Adsorption of chlortetracycline from aqueous solution by chitin - Tunc, Muskun Sara; Hanay, Ozge; Yildiz, Burcin (Taylor & Francis Inc, 2020)
In this study, the performance of chitin for removing chlortetracycline (CTC) from aqueous solutions was assessed. The effects of pH, chitin dose, CTC concentration and contact time on CTC adsorption by chitin were investigated. The maximum CTC removal efficiency of 82.9% was determined at pH 7, chitin dose of 5 g/L, CTC concentration of 8.8 mg/L and contact time of 120 min. The highest CTC adsorption capacity was found as 12.01 mg/g for CTC of 82.2 mg/L concentration at pH 7. The results demonstrated that CTC removal efficiency decreased from 82.9% to 73.0% with increasing CTC concentration from 8.8 to 82.2 mg/L. The equilibrium data for CTC adsorption indicated a good fit to the Freundlich isotherm model. Pseudo-second-order kinetic model was the best model for describing the adsorption reactions.
Keywords: Adsorption; antibiotic; chlortetracycline; chitin; kinetics; isotherm